2015
DOI: 10.1016/j.chemphyslip.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characterization of asolectin–genistein liposomal system: An approach to analyze its in vitro antioxidant potential and effect in glioma cells viability

Abstract: In this study, the interaction between soy isoflavone genistein and asolectin liposomes was investigated by monitoring the effects of isoflavone on lipidic hydration, mobility, location and order. These properties were analyzed by the following techniques: horizontal attenuated total reflection Fourier transform infrared spectroscopy (HATR-FTIR), low-field (1)H nuclear magnetic resonance (NMR), high-field (31)P NMR, zeta potential, differential scanning calorimetry (DSC) and UV-vis spectroscopy. The antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 98 publications
1
26
0
Order By: Relevance
“…Slight reduction in ABTS values in PGloaded liposomes was found with respect to the corresponding phenolic extract (PG in aqueous solution). This loss of activity could be due to partial degradation of phenolic compounds during liposome preparation or to less availability of reactive groups resulting from interactions with the bilayer membrane (Lopes de Azambuja et al, 2015). In contrast, HC became apparently more antioxidant when included in liposomes, with around a 4-fold increase in ABTS value (from 20.36 to 90.40 VCEAC mg/g bioactive).…”
Section: Free and Encapsulated Active Compoundsmentioning
confidence: 98%
“…Slight reduction in ABTS values in PGloaded liposomes was found with respect to the corresponding phenolic extract (PG in aqueous solution). This loss of activity could be due to partial degradation of phenolic compounds during liposome preparation or to less availability of reactive groups resulting from interactions with the bilayer membrane (Lopes de Azambuja et al, 2015). In contrast, HC became apparently more antioxidant when included in liposomes, with around a 4-fold increase in ABTS value (from 20.36 to 90.40 VCEAC mg/g bioactive).…”
Section: Free and Encapsulated Active Compoundsmentioning
confidence: 98%
“…decreases its mobility, and rigidified the hydrophobic part of the asolectine liposomes [35]. It also was found that isoflavone prevents lipid molecules from peroxidation [35].…”
Section: Spectroscopic Analyses -Developments and Applications 40mentioning
confidence: 99%
“…In addition, PEG is biocompatible, which enables the possibility of further functionalization of the liposomes by attaching antibodies or ligands [33,34]. The 31 P spectra analysis of PEGylated liposomes obtained using the thin film method revealed information about the amount of free lipids or building micelles (narrow line) and lipids building MLV (broad shoulder) [31,35]. It is also possible to obtain more than one narrow signal ( Figure 2).…”
Section: Lipid Membrane Dynamic Studiesmentioning
confidence: 99%
“…This is probably due to the fact that in high concentrations, the xanthohumol intends to be replaced in the core of liposome, thus, it becomes less accessible for scavenging. Slight degradation during liposome preparation and relatively low yield of encapsulation can be other explanations for this reduction (Lopes de Azambuja et al, ).…”
Section: Resultsmentioning
confidence: 99%